Cerebrospinal Fluid Levels of Phosphorylated Neurofilament Heavy as a Diagnostic Marker of Canine Degenerative Myelopathy. (10th February 2017) - Toedebusch, C.M.; Bachrach, M.D.; Garcia, V.B.; Johnson, G.C.; Katz, M.L.; Shaw, G.; Coates, J.R.; Garcia, M.L.
Abstract : Background: No definitive, antemortem diagnostic test for canine degenerative myelopathy (DM) is available. Phosphorylated neurofilament heavy (pNF‐H) is a promising biomarker for nervous system diseases. Hypothesis/Objective: Cerebrospinal fluid (CSF) and serum pNF‐H is a detectable biological marker for diagnosis of canine DM. Animals: Fifty‐three DM‐affected, 27 neurologically normal, 7 asymptomatic at‐risk, and 12 DM mimic dogs. Methods: Archived CSF and serum pNF‐H concentrations were determined by a commercially available ELISA. A receiver‐operating characteristic (ROC) curve was generated with CSF values. Results: Compared with old control dogs, median CSF pNF‐H concentration was increased in all stages of DM; old dogs 5.1 ng/mL (interquartile range [IQR] 1.4–9.3) versus DM stage 1 23.9 ng/mL (IQR 20.8–29.6; P < .05) versus DM stage 2 36.8 ng/mL (IQR 22.9–51.2; P < .0001) versus DM stage 3 25.2 ng/mL (IQR 20.2–61.8; P < .001) versus DM stage 4 38.0 ng/mL (IQR 11.6–59.9; P < .01). Degenerative myelopathy stage 1 dogs had increased median CSF pNF‐H concentrations compared with asymptomatic, at‐risk dogs (3.4 ng/mL [IQR 1.5–10.9; P < .01]) and DM mimics (6.6 ng/mL [IQR 3.0–12.3; P < .01]). CSF pNF‐H concentration >20.25 ng/mL was 80.4% sensitive (confidence interval [CI] 66.09–90.64%) and 93.6% specific (CI 78.58–99.21%) for DM. Area under the ROC curve was 0.9467 (CI 0.92–0.9974). No differences in serum pNF‐H concentration were found between control and DM‐affected dogs. Conclusions and Clinical Importance: pNF‐H concentration in CSF is a sensitive biomarker for diagnosis of DM. Although there was high specificity for DM in this cohort, further study should focus on a larger cohort of DM mimics, particularly other central and peripheral axonopathies.